IMPLEMENTASI HUKUM KELUARGA ISLAM DI ACEH BESAR DALAM MERESPON PERUBAHAN SOSIAL - Sayed Ilyas, Sayed Ilyas; Zahrul Fatahillah; Muhammad Zulfan (Sekolah Tinggi Ilmu Syari'ah (STIS) Nahdlatul Ulama Aceh, 2024)
Islamic family law plays an important role in shaping the social structure of Muslims and has undergone formalization in Indonesia's national legal system. However, its implementation in the field faces various obstacles, such as nikah siri, unauthorized polygamy and illegal divorce. This phenomenon indicates a gap between legal norms and social reality. This study aims to examine the factors inhibiting the implementation of Islamic family law in Aceh Besar and its response to social dynamics. This study is expected to provide solutions to the problems of Islamic family law in the context of Indonesian legal pluralism. The research method used in this study is empirical juridical legal research, which is research that not only examines the law as a written norm (das sollen), but also analyzes how the law applies and is implemented in social reality (das sein). The results showed multidimensional obstacles, ranging from low legal literacy, patriarchal culture, to disharmonization between qanun and national law. Limited access to the judiciary and a lack of legal aid also exacerbate inequalities in justice. In addition, weak institutional coordination and lack of evaluation lead to policy stagnation. Responses to social change, including digitalization and gender awareness, have not been fully accommodated. A transformative and participatory approach is needed in strengthening family law. This research recommends systemic reforms that include legal education, harmonization of rules, and increased access to justice based on equality and maqāṣid sharia.